A Super‐Hydrophobic Quasi‐Solid Electrolyte for Li‐O2 Battery with Improved Safety and Cycle Life in Humid Atmosphere. Issue 4 (3rd November 2016) - Wu, Shichao; Yi, Jin; Zhu, Kai; Bai, Songyan; Liu, Yang; Qiao, Yu; Ishida, Masayoshi; Zhou, Haoshen
Abstract : A super‐hydrophobic quasi‐solid electrolyte for Li‐O2 battery is built to enable the merit of water catalysis assisting for battery performance improvement and prevent Li corrosion by H2 O crossover from cathode. The battery in humid atmosphere can achieve low charge potential (≈3.4 V) and long cycle life (150 discharge–charge cycles).